2016
DOI: 10.5455/msm.2016.28.104-107
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Maternal Serum Zinc, Iron, Calcium and Magnesium During Pregnancy in Pregnant Women and Umbilical Cord Blood and their Association with Outcome of Pregnancy

Abstract: Background:Trace elements and specially minerals are critical for the development of fetus. Many minerals are transferred to the fetus for fetal stores in the latter part of the pregnancy. It has been shown that various trace elements such as Zinc, Iron, Calcium and Magnesium are metabolically interrelated and there is alteration in their concentration during pregnancy. Beyond pregnancy is associated with increased demand of all the nutrients and deficiency of any of these could affect pregnancy, delivery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
3
30
2
1
Order By: Relevance
“…Previous studies on dietary and supplemental zinc showed a potential protective effect on type 2 diabetes [30].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies on dietary and supplemental zinc showed a potential protective effect on type 2 diabetes [30].…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that various trace elements such as Ca, P, Mg, Zn, Cu, Fe, etc. are metabolically interrelated, and there is an alteration in their concentration during pregnancy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the currently available data suggests a positive correlation between the concentration of iron in the maternal serum and the birth weight of neonates (Table 2) [6,7]. According to Wang et al, the impact of iron supplementation in pregnancy on the birth weight of the child depends on the concentration of hemoglobin in maternal blood before pregnancy [9].…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency can result in abnormalities in brain development and cogni- 74.4 ± 12.1 [7] 63.5 ± 15.2 [1] 79.3 ± 8.6 [7] 70.1 ± 14.4 [1] 82.2 ± 10.2 [7] Zn 79.5 ± 15 [1] 74.9 ± 9.1 [7] 74.5 ± 16.1 [1] 73.1 ± 10.6 [7] 65.3 ± 14.9 [1] 68.4 ± 9.9 [7] Mn ---Cu 130.9 ± 43.5 [1] 172.0 ± 38.94 [1] 193.2 ± 28.5 [1] Se ---tive impairment later on in life. Tissue iron stores depletion can lead to cellular hypoxia, which could lead to the abnormal proliferation of blood vessels in order to compensate for the oxygen deficiency in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation